2021
DOI: 10.3389/fpsyt.2021.777447
|View full text |Cite
|
Sign up to set email alerts
|

The Deficits of Individual Morphological Covariance Network Architecture in Schizophrenia Patients With and Without Violence

Abstract: Background: Schizophrenia is associated with a significant increase in the risk of violence, which constitutes a public health concern and contributes to stigma associated with mental illness. Although previous studies revealed structural and functional abnormalities in individuals with violent schizophrenia (VSZ), the neural basis of psychotic violence remains controversial.Methods: In this study, high-resolution structural magnetic resonance imaging (MRI) data were acquired from 18 individuals with VSZ, 23 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…We recruited 45 patients with schizophrenia who had engaged in serious violent behaviors and referred to the forensic psychiatry department of the Second Xiangya Hospital (China) for examination. According to previous study [ 16 ], the present research defined violence as behaviors causing severe physical injuries to others, including homicide and other serious assaults. What’s more, for better quantitative description, we also required that the scores of the Modified Overt Aggression Scale (MOAS) to be more than 4 in the group of VSC [ 8 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recruited 45 patients with schizophrenia who had engaged in serious violent behaviors and referred to the forensic psychiatry department of the Second Xiangya Hospital (China) for examination. According to previous study [ 16 ], the present research defined violence as behaviors causing severe physical injuries to others, including homicide and other serious assaults. What’s more, for better quantitative description, we also required that the scores of the Modified Overt Aggression Scale (MOAS) to be more than 4 in the group of VSC [ 8 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Volume alterations in the limbic system, especially in the hippocampus and amygdala, are also reported in some studies [ 14 , 15 ]. A study reported decreased GMV of the hypothalamus in patients with VSC, compared to NSC and HC [ 16 ], and the GMV of the hypothalamus was found negatively correlated with the scores of PANSS and MOAS. Furthermore, reduced bilateral hippocampal GMV was also found in patients with SCZ who committed homicide, as compared to those with NSC and HC [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the method of constructing an individual specialized SCN was introduced to depict subject-specific covariance variability in healthy people ( Zhao et al, 2021 ) and to outline covariance alterations in neuropsychiatric disease patients ( Liu et al, 2021 ; Shen et al, 2021 ; Han et al, 2022 ). The individualized SCN is measured according to the correlation of multiple morphometric features ( Li et al, 2017 ; Seidlitz et al, 2018 ; Morgan et al, 2019 ; Zhao et al, 2021 ), regional probability density distribution ( Kong et al, 2014 ; Wang et al, 2016 ) or network perturbation approaches ( Kim et al, 2016 ; Wolfers et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%